STRENGTHENING PALM OIL AGRIBUSINESS TRACEABILITY SYSTEMS TO ADDRESS VIRAL CONCERNS ON SUPPLY CHAIN TRANSPARENCY AND ENVIRONMENTAL ACCOUNTABILITY - Hamdani Hamdani; Elfi Rahmadani; Agus Suprapto; Linda Umasugi; Dheny Arina Hartawaty (SOSIOEDUKASI, 2026)
The palm oil industry is one of the most important global agribusiness sectors, playing a significant role in meeting the world’s demand for vegetable oil while supporting economic growth in producing countries, particularly Indonesia. However, the expansion of oil palm plantations is often associated with environmental issues such as deforestation, land degradation, and biodiversity loss, which have triggered global concerns regarding supply chain transparency and environmental accountability. This study aims to analyze and formulate strategies for strengthening traceability systems in the palm oil agribusiness sector in order to improve supply chain transparency and environmental accountability. The research employs a qualitative approach using a literature review method based on academic journals, books, international organization reports, and policy documents related to palm oil sustainability and supply chains. Data were analyzed using content analysis and thematic analysis to identify key concepts, research patterns, and strategic approaches to strengthening traceability systems. The results indicate that supply chain complexity, the involvement of smallholder farmers, and limited data integration remain major challenges in traceability implementation. Therefore, strengthening traceability systems through digital technology adoption, improved governance, and stakeholder collaboration is essential to enhance transparency and environmental accountability in the palm oil industry.